Aplikasi Administrasi Pengarsipan Surat Menyurat di IBI Darmajaya - amnah, Amnah (Jurnal Informatika, 2010)
The Business Correspondence that currently run by Informatics and Business Damajaya is still using decentralization and manual system. Along with the upraising of business intensity level, particularly the flow of letter circulation, this system seems to be out of date or does not match with the demand, therefore, a new good application of business letters is urgently needed to replace the old one. Letter Application is a process of computerization of manual data to facilitate the process toward the target and minimize error and hindrance. Keyword : Administration, Archives, Information